MENGOPTIMALKAN HASIL BELAJAR MATEMATIKA MELALUI DISCOVERY LEARNING BERBANTUAN EDUCAPLAY: BUKTI EMPIRIS PADA SISWA SMP - Dewi Soleha; Musdi, Edwin; Mirna; Harisman, Yulyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on assessing the effectiveness of using Educaplay in learning that applies the Discovery Learning model. A quantitative approach was chosen, using a quasi-experimental method with a posttest-only control group design to examine differences in learning outcomes between the treatment class and the control class. The research subjects were selected using cluster random sampling, resulting in the selection of the experimental class (VII.3) and the control class (VII.1). The research instruments used were quizzes and mathematics achievement tests. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing. The average score obtained by the class that received the treatment was 59.28, while the class that did not receive the treatment scored 44.08. The results of the hypothesis testing indicate that the integration of Educaplay into discovery learning supports an improvement in students’ learning outcomes.